Opportunities for making health financing and services more inclusive in the Philippines. - Picazo, Oscar F. (2013)
This Policy Note identifies opportunities for making health financing and services more inclusive. Many opportunities exist today to make growth more inclusive through improved health financing, regulation and planning, and service delivery. The key is to capitalize on these opportunities while addressing attendant challenges and issues. Economic growth makes it possible for the health budget to increase. The Department of Health (DOH) is keen on expanding health services to address the significant deficits in the number of health facilities and reach of health programs. The Aquino II administration`s health financing reforms (such as the Universal Health Care program) is deliberately designed to focus on the poorest of the poor. There are also promising health market innovations that can significantly improve supply-side response. Lastly, performance benchmarking has been accepted as a norm in the health sector, and several initiatives have been undertaken, including accreditation, seal of good housekeeping, DOH`s balanced score cards, and dashboards.
Keywords: Medical care; Health insurance